Additive Manufacturing in Atomic Layer Processing Mode - Kundrata, Ivan; Barr, Maissa; Tymek, Sarah; Döhler, Dirk; Hudec, Boris; Brüner, Philipp; Vanko, Gabriel; Precner, Marian; Yokosawa, Tadahiro; Spiecker, Erdmann; Plakhotnyuk, Maksym; Fröhlich, Karol; et al. (Small Methods, 2022)
Additive manufacturing (3D printing) has not been applicable to micro- and nanoscale engineering due to the limited resolution. Atomic layer deposition (ALD) is a technique for coating large areas with atomic thickness resolution based on tailored surface chemical reactions. Thus, combining the principles of additive manufacturing with ALD could open up a completely new field of manufacturing. Indeed, it is shown that a spatially localized delivery of ALD precursors can generate materials patterns. In this “atomic-layer additive manufacturing” (ALAM), the vertical resolution of the solid structure deposited is about 0.1 nm, whereas the lateral resolution is defined by the microfluidic gas delivery. The ALAM principle is demonstrated by generating lines and patterns of pure, crystalline TiO2 and Pt on planar substrates and conformal coatings of 3D nanostructures. The functional quality of ALAM patterns is exemplified with temperature sensors, which achieve a performance similar to the industry standard. This general method of multimaterial direct patterning is much simpler than standard multistep lithographic microfabrication. It offers process flexibility, saves processing time, investment, materials, waste, and energy. It is envisioned that together with etching, doping, and cleaning performed in a similar local manner, ALAM will create the “atomic-layer advanced manufacturing” family of techniques.
CRIS-Team Scopus Importer:2022-03-18
Keywords: additive manufacturing; atomic layer deposition; nanofabrication; thin films

Monolithic Two-Terminal Tandem Solar Cells Using Sb2S3 and Solution-Processed PbS Quantum Dots Achieving an Open-Circuit Potential beyond 1.1 V - Kern, Selina; Yi, Gyusang; Büttner, Pascal; Scheler, Florian; Tran, Minh Hoa; Korenko, Sofia; Dehm, Katharina; Kundrata, Ivan; Zahl, Achim; Albrecht, Steve; Bachmann, Julien; Crisp, Ryan (ACS Applied Materials and Interfaces, 2024)
Multijunction solar cells have the prospect of a greater theoretical efficiency limit than single-junction solar cells by minimizing the transmissive and thermalization losses a single absorber material has. In solar cell applications, Sb2S3 is considered an attractive absorber due to its elemental abundance, stability, and high absorption coefficient in the visible range of the solar spectrum, yet with a band gap of 1.7 eV, it is transmissive for near-IR and IR photons. Using it as the top cell (the cell where light is first incident) in a two-terminal tandem architecture in combination with a bottom cell (the cell where light arrives second) of PbS quantum dots (QDs), which have an adjustable band gap suitable for absorbing longer wavelengths, is a promising approach to harvest the solar spectrum more effectively. In this work, these two subcells are monolithically fabricated and connected in series by a poly(3,4-ethylene-dioxythiophene) polystyrene sulfonate (PEDOT:PSS)-ZnO tunnel junction as the recombination layer. We explore the surface morphology of ZnO QD films with different spin-coating conditions, which serve as the PbS QD cell’s electron transport material. Furthermore, we examine the differences in photogenerated current upon varying the PbS QD absorber layer thickness and the electrical and optical characteristics of the tandem with respect to the stand-alone reference cells. This tandem architecture demonstrates an extended spectral response into the IR with an open-circuit potential exceeding 1.1 V and a power conversion efficiency of 5.6%, which is greater than that of each single-junction cell.
CRIS-Team Scopus Importer:2024-03-29
Keywords: antimony sulfide; atomic layer deposition; chalcogenide solar cells; lead sulfide; mapping ellipsometry; multijunction; nanocrystals; recombination layer

Sb2Se3Thin-Film Growth by Solution Atomic Layer Deposition - Koch, Vanessa; Charvot, Jaroslav; Cao, Yuanyuan; Hartmann, Claudia; Wilks, Regan G.; Kundrata, Ivan; Minguez Bacho, Ignacio; Gheshlaghi, Negar; Hoga, Felix; Stubhan, Tobias; Alex, Wiebke; Pokorný, Daniel; et al. (Chemistry of Materials, 2022)
We establish solution atomic layer deposition (sALD) for the controlled growth of pure Sb2Se3 thin films under mild conditions, namely, room temperature and atmospheric pressure. Upscaling this process yields Sb2Se3 thin films with high homogeneity over large-area (4″) substrates. Annealing of the initially amorphous material leads to highly crystalline and smooth Sb2Se3 thin films. Removing the constraints of thermal stability and sufficient volatility in sALD compared to traditional gas-phase ALD opens up a broad choice of precursors and allows us to examine a wide range of Se2- precursors, of which some exhibit facile synthetic routes and allow us to tune their reactivity for optimal experimental ease of use. Moreover, we demonstrate that the solvent used in sALD represents an additional, attractive tool to influence and tailor the reactivity at the liquid-solid interface between the precursors and the surface.
Created from Fastlane, Scopus look-up